Diagnostic features of the presumed focal viral retinitis: A case series - Manandhar, Anu (Nepalese Journal of Ophthalmology, 2020)
Introduction: Other than well-known herpetic retinopathies like acute retinal necrosis, progressive outer retinal necrosis and cytomegalovirus retinitis, there are few reports on atypical forms of viral retinitis caused by herpes virus from around the world. Cases: Presenting symptom was sudden onset of diminution of vision in all 6 cases. Mean duration of symptoms at presentation was 7.6 days. The mean age was 27.3 years (range 22-40 years). All were immunocompetent (4 females and 2 males), with unremarkable review of system. All had unilateral involvement. Presenting visual acuity ranged from CFCF to 6/60. Granulomatous anterior uveitis was present in 4 cases. All had focal retinitis with irregular margins, either juxtapapillary, macular or over one of the major vascular arcades. The diagnosis of focal viral retinitis was made solely based upon the clinical findings. All recovered after a course of oral acyclovir (one was given additional intravitreal acyclovir as well) and oral prednisolone, with final visual acuity of 6/6P to 6/9 in all except one. Conclusion: In case of focal retinitis with irregular margin, viral etiology should be borne in mind. Clinical features are typical enough to help in diagnosing without PCR test.